Renditions of Anselm’s Ontological Argument in Modern Philosophy of the West - hamid Parsania (حکمت اسرا)
Saint Anselm’s eleventh century argument for the existence of God was revisited by modern Western philosophers from the 17th century onwards, leading to such figures as Descartes, Spinoza, Leibnitz, Hume, and Kant, each in his turn, giving their rendition and either defending or critiquing it. The present article surveys the discussions that took place regarding Anselm’s argument in Western philosophical circles from the 17th century up until the present from the viewpoint of Islamic philosophy.